THE USE OF RELATIVE CLAUSES AS THE POST MODIFIERS OF THE NOUN PHRASE CONSTRUCTIONS IN THE STUDENTS’ THESIS BACKGROUND - Jessica Febrina Haryanto; Hendra Tedjasuksmana (Widya Mandala Surabaya Catholic University, 2022)
This study concerns on how the undergraduate students of the English Language Education Study Program use relative clauses as the post modifiers of the noun phrases in their thesis background and the errors found and their causes in the noun phrase constructions. Thirty undergraduate students were asked to be the subjects and the data were taken from their thesis backgrounds. The total of 226 noun phrases with relative clauses as the post modifiers were constructed with ten errors found. From the interviews conducted with fifteen subjects, the errors found were caused by (1) the different structures of English grammar point (the noun phrases with relative clauses as the post modifiers) with the Indonesian, (2) the gap time of the teaching and learning activities of the grammar concept that caused the students to forget about the structures, and (3) the pace of the students’ learning which did not match with the lecturers’ teaching pace. The results show that even though the awareness of the students was moderately high, they need to be reminded and encouraged to produce more complex sentences with noun phrases with relative clauses as the post modifiers to improve their thesis background.